If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9x-1=-4x-2
We simplify the equation to the form, which is simple to understand
-9x-1=-4x-2
We move all terms containing x to the left and all other terms to the right.
-9x+4x=-2+1
We simplify left and right side of the equation.
-5x=-1
We divide both sides of the equation by -5 to get x.
x=0.2
| 6x^3+72x^2-78x=0 | | 7m+4m=77 | | 5=-8.7+6x | | f(x)=5cos(x) | | 3/4=15/x2 | | -4x^2-52x+120=0 | | 3(x-5)2(x-1)=8 | | 4(5x+4)=236 | | 8t+48t+t^2= | | 2x^3-32x^2+78x=0 | | 2w-4=4 | | 7-3*2+6+3=35 | | 1.86=6.2a | | 25x^3-15x^4=5x^3 | | -30+5(x-2)=4x+7 | | 9-7x=42+(-4x) | | 3x^2-58x-40=0 | | 3ab-2b=3a-b | | -3x^2-3x+90=0 | | 1.2y-0.3x=0.12 | | -7x-5y=11 | | X/11=-22 | | f(x)=2x^2-16x+27 | | 3Y-9-3Y=-9 | | 1.2x-0.3y=0.12 | | 12-7x=9x-5x-87 | | 4x^3+72x^2+68x=0 | | 5/6-x/6=6/5 | | 2^3*x=1/64 | | 3x-5x+4-x+7=88 | | -3x+8=5x-2 | | -x^3+10x^2+39x=0 |